2019
DOI: 10.1063/1.5054025
|View full text |Cite
|
Sign up to set email alerts
|

Properties of high-energy electron beams trap with a magnetic mirror field

Abstract: The properties of a high energy short pulse electron beam in a magnetic mirror field are studied numerically by the Particle-in-Cell method. The complex nature of processes studied, and also the need for the calculation of the positions, velocities, and trajectories of billions of particles, required the use of a scalable parallel algorithm. The use of modern supercomputers has allowed us to calculate the plasma dynamics, to determine the electron beam in the magnetic mirror field. Mathematical modeling of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The dependence of the loss rate of the charged particles on the system parameters for an axial symmetric mirror has been studied previously [9,10]. It is reported that the loss rate decreases as the mirror ratio increases [10].…”
Section: The Confinement Of Proton Beam In a Bent Mirrormentioning
confidence: 99%
See 4 more Smart Citations
“…The dependence of the loss rate of the charged particles on the system parameters for an axial symmetric mirror has been studied previously [9,10]. It is reported that the loss rate decreases as the mirror ratio increases [10].…”
Section: The Confinement Of Proton Beam In a Bent Mirrormentioning
confidence: 99%
“…For the axi-symmetric mirror, the loss of particles is mainly caused in the axis direction. Furthermore, the larger the magnetic mirror ratio R m (R m = B m /B 0 , B m and B 0 are the maximum and minimum of the strength of magnetic field on the axis respectively), the less the loss of particles [9,10,26,27]. Figure 5(a) shows the dependence of the strength of magnetic field on the spatial coordinate x for y = 0 and y = ±0.035 m, with α = 0 and α = 45°respectively.…”
Section: The Confinement Of Proton Beam In a Bent Mirrormentioning
confidence: 99%
See 3 more Smart Citations